Response of soybean (Glycine max L.) genotypes to varying levels of phosphorus for yield and related traits under acid soils of western Ethiopia - Abebe, A.T.; Githiri, M.; Derera, J.; Debele, T. (2018)
Low availability of soil phosphorus (P) is one of the major limiting factors for soybean production on acidic soils of the tropics. The objectives of this study were to assess the interaction of soybean genotypes (G) with levels of P, and identify genotypes that are responsive to high P and tolerant to low P conditions. A total of 36 soybean genotypes were evaluated under three levels of P (0, 100, and 200 kg ha-1) in three locations (L) of Western Ethiopia in split plot design with P levels as main plots, and genotypes as subplots. The individual locations analysis, revealed that the genotypes X phosphorus interaction for grain yield was significant (P<0.05) at Assosa. The genotypes showed highly significant differences for most of the studied traits in all the locations. The combined analysis revealed that there was significant G, and LXG interactions for most of the traits. Essex-1, IAC 11 and AGS-3-1 were the best performing genotypes on 200 kg ha-1 P; while IAC 11, AA-7138, G 9945 and Hawassa 04 exhibited tolerance to low P. AMMI analysis for grain yield at Assossa revealed that zero and 200 kg ha-1 were highly interactive with the genotypes. Genotypes: AA-7138, PR-142 (26) and H 3 were stable genotypes across the P levels with relatively high main effect; and hence, such genotypes are useful in breeding soybeans for consistent response to varying P conditions.